Branding Through Interior Design: Exploring Theory, and Interpretation - R Mekar Liza Ramadhina; Susy Budi Astuti (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
The theory of interior branding is a concept proposed by Kim Kuhteubl (2016) in her book